Dissecting and Evaluating the Therapeutic Targets of Coptis Chinensis Franch in the Treatment of Urinary Tract Infections Induced by Escherichia coli - Chang, Zhenglin; Zhang, Jinhu; Lei, Min; Jiang, Zheng; Wu, Xiangkun; Huang, Yapeng; He, Zhican; Zhang, Yuyan; Li, Shujue; Duan, Xiaolu; Wu, Wenqi (Frontiers in Pharmacology, 2022)
Coptis chinensis Franch (CCF) is extensively used in the treatment of inflammatory-related diseases. Accumulating studies have previously demonstrated the anti-inflammatory properties of CCF, yet data on its exact targets against urinary tract infections (UTIs) remain largely unknown. Therefore, the present study decodes potential targets of action of CCF against UTIs by network pharmacology combined with experiment evaluations. Based on the pharmacology network analysis, the current study yielded 6 core ingredients: quercetin, palmatine, (R)-Canadine, berlambine, berberine, and berberrubine. The protein-protein interaction network (PPI) was generated by the String database and then four targets (IL6, FOS, MYC, and EGFR) were perceived as the major CCF targets using the CytoNCA plug-in. The results of molecular docking showed that the 6 core constituents of CCF had strong binding affinities towards the 4 key targets of UTIs after docking into the crystal structure. The enrichment analysis indicated that the possible regulatory mechanisms of CCF against UTIs were based on the modules of inflammation, immune responses, apoptosis among others. Experimentally, the Escherichia coli (E. coli) strain CFT073 were applied to establish in vivo and in vitro model. In vivo results revealed that the key targets, IL6 and FOS are significantly upregulated in rat bladder tissues of UTIs whereas the expression of MYC and EGFR remained steady. Lastly, in vitro results further confirmed therapeutic potential of CCF by reducing the expression of IL6 and FOS. In conclusion, the IL6 and FOS were generally upregulated in the progression of E. coli-induced UTIs, whereas the CCF intervention exerted a preventive role in host cells stimulated by E. coli partially due to inhibiting the expression of IL6 and FOS.